High temperature resistant fluorine-containing ion exchange resin dispersion and method for producing the same
Patent Information
- Application Number
- CN202311638556.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-18
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2042-10-18
AI Technical Summary
然而聚乙烯醇所具有的C-H键键能低于C-F键键能,其耐高温和化学腐蚀性不如全氟结构要好
[0081]1、本发明所提供的耐高温功能聚合物中包含全氟乙烯膦酸聚合单元以及两种不同结构的全氟烯醚磺酸聚合单元,三种聚合单元共同作用,提供了共同解决了现有技术中树脂聚合物在高温(110℃~150℃)条件下电阻率高的问题,本发明所提供的耐高温功能聚合物在150℃条件下的电阻率不高于16mS/cm。
Smart Images

Figure CN117683166B_ABST
Abstract
Description
[0001] This application is a divisional application of application No. 202211272321.8 (filed on 2022-10-18, entitled "High Temperature Resistant Functional Polymer"). Technical Field
[0002] This invention belongs to the field of fluorine-containing polymer materials, specifically relating to a high-temperature resistant fluorine-containing ion exchange resin dispersion and its preparation method. Background Technology
[0003] Since DuPont successfully developed perfluorosulfonic acid ion exchange resins in the 1970s, ion exchange membranes made from these resins have been applied in the chlor-alkali industry and proton exchange membrane fuel cells. Due to their unique properties, they have attracted widespread attention from researchers worldwide. Perfluorinated ion exchange resins, especially fluorinated ion exchange membranes containing sulfonic acid and carboxylic acid groups, possess stable resistance to chemical degradation and ionic conductivity, making them suitable for use as electrochemical membranes in fuel cells and chlor-alkali electrolyzers.
[0004] In fuel cell applications, a key requirement for the membrane electrode assembly (MEA), formed by the ion exchange membrane and catalyst layer, is its chemical stability and resistance to carbon monoxide (CO) poisoning. Currently, the most widely used catalyst coating resin is perfluorosulfonic acid resin from DuPont, which has a carbon-fluorine backbone and side chains with sulfonic acid groups. Because its proton conduction relies on water molecules, its proton conductivity decreases significantly above 80°C. However, at 80°C, the catalyst layer of the MEA will exhibit poisoning behavior in environments with CO concentrations reaching 10 ppm. To address the current difficulties in fuel cell MEAs, such as improving catalyst activity and utilization, and enhancing the catalyst layer's resistance to CO poisoning, an effective solution is to increase the operating temperature of the fuel cell. Above 100°C, the catalyst's tolerance to CO in the MEA increases to approximately 1000 ppm. Water is a crucial medium for proton conduction in proton exchange membranes. However, when the operating temperature of fuel cell membranes exceeds 100°C, the membrane's water retention capacity decreases significantly, leading to a marked reduction in proton conductivity. At operating temperatures of 120°C, the proton conductivity drops far below 0.01 S / cm, failing to meet the requirements for ion conduction. In summary, the catalyst's requirement for the highest possible operating temperature to avoid CO poisoning contradicts the fact that existing membrane electrode assemblies can only operate at lower temperatures.
[0005] Furthermore, high-temperature fuel cells offer higher catalyst efficiency, simplified water / heat management, and better resistance to fuel impurities, which can reduce the cost of fuel cell systems and better meet the requirements of fuel cell commercialization. Currently, major countries conducting fuel cell research are investing significant human and material resources in this area. The long-side-chain sulfonic acid resins currently used in the fuel cell field do not meet requirements in various aspects, including high-temperature oxidation resistance, high-temperature proton conductivity, water retention, and temperature resistance, especially in terms of high-temperature proton conductivity and water retention.
[0006] To improve the proton conductivity and water retention of sulfonic acid resins under high temperature and low humidity conditions, Chinese patent CN113429715A discloses a phosphorylated polyvinyl alcohol / perfluorosulfonic acid resin composite. An ion exchange membrane is prepared by blending phosphorylated polyvinyl alcohol with perfluorosulfonic acid resin to improve the proton transport capacity and water absorption of the proton exchange membrane under high temperature and low humidity conditions. However, the CH bond energy of polyvinyl alcohol is lower than that of the CF bond energy, and its high temperature resistance and chemical corrosion resistance are not as good as those of the perfluoro structure. Summary of the Invention
[0007] To improve the operating temperature of fuel cells, it is necessary to develop a high-temperature resistant polymer that also has proton exchange functionality to overcome the challenges faced by proton exchange membranes in fuel cells. This invention synthesizes a gas-permeable and high-temperature resistant polymer by using short-side-chain perfluorosulfonyl fluoride monomers, perfluorophosphonate monomers, and fluorinated olefins in a multi-component copolymerization process. This polymer is particularly suitable for catalyst coatings. The successful implementation of this invention will lead to revolutionary hydrogen fuel cell technology and drive profound changes in the global hydrogen energy application field.
[0008] The above-mentioned objective of this invention is achieved by the following technical solution:
[0009] This invention provides a high-temperature resistant functional polymer, obtained by hydrolysis and acidification of a precursor polymer obtained by multi-component copolymerization of fluorinated olefins, perfluoroethylene phosphonate monomers, perfluorovinyl ether sulfonyl fluoride monomers, and perfluoroheterocyclic olefin ether sulfonyl fluoride monomers. The structural formula of the high-temperature resistant functional polymer is as follows:
[0010]
[0011] in,
[0012] g is an integer from 1 to 4, preferably g = 2;
[0013] t is an integer from 0 to 3, and v is an integer from 1 to 4, preferably t = 1 and v = 2;
[0014] a, b, and c are integers from 1 to 20, and a', b', and c' are integers from 1 to 3.
[0015] The x, y, and z satisfy the following conditions: x / (x+y+z)=0.6-0.8, y / (x+y+z)=0.1-0.2, z / (x+y+z)=0.1-0.2;
[0016] The R is —(OCF2) e (CF2) f X, where X is either Cl or F; where e is an integer from 0 to 1, and f is an integer from 0 to 1; R1 is Or —CF—CF—;
[0017] R f for
[0018] Where m and n are integers from 0 to 4, and m and n are not both 0.
[0019] The structural formula of the precursor polymer is:
[0020]
[0021] In the formula, g is an integer from 1 to 4, preferably g = 2; t is an integer from 0 to 3; v is an integer from 1 to 4, preferably t = 1 and v = 2; a, b, and c are integers from 1 to 20; a', b', and c' are integers from 1 to 3. x / (x+y+z) = 0.6-0.8, y / (x+y+z) = 0.1-0.2, z / (x+y+z) = 0.1-0.2. q is an integer from 2 to 3.
[0022] R is —(OCF2) e (CF2) f X, where X is either Cl or F, and e is an integer from 0 to 1, and f is an integer from 0 to 1.
[0023] R1 is Or —CF—CF—, R f1 for Where m and n are integers from 0 to 4, and m and n are not both 0.
[0024] The structural formula of the perfluorovinyl ether sulfonyl fluoride monomer is:
[0025]
[0026] Where t is an integer from 0 to 3, and v is an integer from 1 to 4, preferably t = 1 and v = 2.
[0027] The structural formula of the perfluorinated heterocyclic olefin ether sulfonyl fluoride monomer is:
[0028]
[0029] In the formula, R 11 for Or —CF = CF —, R f1 for Where m and n are integers from 0 to 4, and m and n are not both 0.
[0030] The structural formula of the perfluoroethylene phosphonate monomer is:
[0031]
[0032] Where g is an integer from 1 to 4, preferably g = 2; q is an integer from 2 to 3.
[0033] The high-temperature resistant functional polymer has the structural formula of an ionic group obtained by hydrolyzing and acidifying the precursor polymer, wherein the ionic group is in an acidic form.
[0034] The number average molecular weight of the above polymer is 100,000 to 800,000, preferably 100,000 to 600,000, more preferably 150,000 to 400,000, and even more preferably 200,000 to 370,000.
[0035] The percentage of molar content of each polymer unit in the precursor polymer is as follows: 60-80% for fluorinated olefin polymer units, 5-20% for perfluoroethylene phosphonate polymer units, 5-20% for perfluorovinyl ether sulfonyl fluoride polymer units, and 5-20% for perfluoroheterocyclic olefin ether sulfonyl fluoride polymer units.
[0036] Preferably, the molar percentage of each polymer unit in the copolymer is as follows: 70-80% for fluorinated olefin polymer units, 6-20% for perfluorinated vinyl ether sulfonyl fluoride polymer units, 6-20% for perfluorinated heterocyclic olefin ether sulfonyl fluoride polymer units, and 6-20% for perfluorinated phosphonate polymer units.
[0037] Preferably, the molar ratio of the perfluorovinyl ether sulfonyl fluoride polymer unit to the perfluoroheterocyclic olefin ether sulfonyl fluoride polymer unit is (0.2:0.8) to (0.8:0.2), and more preferably (0.4:0.6) to (0.6:0.4).
[0038] This invention provides a method for preparing the above-mentioned temperature-resistant functional polymer, the method comprising:
[0039] S1: The above-mentioned fluorinated olefin, perfluoroethylene phosphonate monomer, perfluorovinyl ether sulfonyl fluoride monomer and perfluoroheterocyclic olefin ether sulfonyl fluoride monomer are copolymerized under the action of an initiator to obtain the precursor polymer.
[0040] S2: The precursor polymer is subjected to transformation reactions with alkali and acid respectively to obtain a high-temperature resistant functional polymer.
[0041] In step S1, the initiator may be selected from one or more of peroxides, perfluoroalkyl peroxides, N2F2, azo compounds or persulfates, and redox systems.
[0042] Preferably, the initiator is selected from one or more of N2F2, peroxides, azo compounds and redox initiation systems, or from one or more of N2F2, perfluoroalkyl peroxides or persulfates;
[0043] The perfluoroalkyl peroxide is, in particular, perfluoropropionyl peroxide, 3-chlorofluoropropionyl peroxide, or perfluoromethoxyacetyl peroxide. -H-perfluorobutyryl peroxide, -SO2F-perfluoro-2,5,8-trimethyl-3,6,9-trioxa-undecyl peroxide, CF3CF2CF2CO-OO-COCF2CF2CF3, CF3CF2CF2OCFCF3CO-OO-COCFCF3OCF2CF2CF3, CF3CF2CH2CO-OO-COCH2CF2CF3 or CF3OCF2CF2CO-OO-COCF2CF2OCF3; the persulfate is selected from ammonium persulfate, alkali metal sulfides or alkaline earth metal persulfates; more preferably, the persulfate is selected from ammonium persulfate or potassium persulfate.
[0044] The copolymerization reaction takes 0.5-48 hours, at a temperature of 0-100℃, and at a pressure of 0.01-10MPa.
[0045] Preferably, the copolymerization reaction time is 0.5 to 24 hours, the reaction temperature is 10 to 80°C, and the reaction pressure is 0.2 to 5 MPa.
[0046] More preferably, the copolymerization reaction time is 0.5 to 8 hours, the reaction temperature is 10 to 70°C, and the reaction pressure is 0.2 to 3 MPa.
[0047] The copolymerization reaction includes a dispersion polymerization reaction carried out in an aqueous phase.
[0048] The dispersion polymerization method is as follows:
[0049] 1) Add pure water, perfluorovinyl ether sulfonyl fluoride monomer, perfluoroheterocyclic olefin ether sulfonyl fluoride monomer, perfluoroethylene phosphonate monomer and dispersant to the reaction vessel;
[0050] 2) Fluoroolefins are introduced into the reactor through a gas metering tank until the reaction pressure is reached;
[0051] 3) The reactor is heated to the reaction temperature, and an initiator is added to the reaction system through a metering pump to initiate the reaction. Fluorinated olefin monomers and initiators are continuously added to the reactor to maintain the above-mentioned reaction pressure and carry out the reaction.
[0052] 4) When the reaction is finished, stop adding initiator and fluorinated olefin monomer to the reactor to obtain a milky white polymer slurry. The liquid material is then fed into the post-processing equipment through the venting system. After demulsification and filtration, white polymer powder is obtained and dried to obtain the precursor polymer.
[0053] Unreacted fluorinated olefin monomers are recovered by venting through the reactor venting pipeline and recovery tank; perfluorovinyl ether sulfonyl fluoride monomers, perfluoroheterocyclic olefin ether sulfonyl fluoride monomers, and perfluoroethylene phosphonate monomers in the filtrate are recovered and reused through the recovery system.
[0054] The dispersant is selected from one or any combination of anionic emulsifiers, nonionic emulsifiers, and reactive emulsifiers.
[0055] Preferably, the anionic emulsifier includes sodium fatty acid, sodium dodecyl sulfate, sodium alkyl sulfonate, and sodium alkyl aryl sulfonate; the nonionic emulsifier includes alkylphenol polyether alcohols, such as one or more of nonylphenol polyoxyethylene ether, polyoxyethylene fatty acid, and polyoxyethylene fatty acid ether; the reactive self-emulsifier includes perfluorosulfonates, perfluorophosphates, or perfluorocarboxylatees, such as potassium perfluorovinyl ether sulfonate, ammonium perfluorovinyl ether sulfonate, and ammonium perfluorovinyl ether phosphonate.
[0056] In the dispersion polymerization, the dispersant has a mass percentage concentration of 5-10% in water, the perfluorovinyl ether sulfonyl fluoride monomer has a mass percentage concentration of 25-30% in water, the perfluoroheterocyclic olefin ether sulfonyl fluoride monomer has a mass percentage concentration of 5-10% in water, and the perfluoroethylene phosphonate monomer has a mass percentage concentration of 45-50% in water.
[0057] In step S2, the alkali is an alkali metal salt or a weak alkali.
[0058] The metal salts include lithium hydroxide, sodium hydroxide, or potassium hydroxide.
[0059] Preferably, the alkali metal salt has a mass percentage concentration of 1-50% in the solution;
[0060] The weak base includes ammonia, ferric hydroxide, and copper hydroxide.
[0061] Preferably, the mass percentage concentration of the weak base in the solution is 1-30%;
[0062] The acid is a strong acid solution, including any one or more common strong acids such as nitric acid, sulfuric acid, etc.
[0063] The concentration is 5-30%, and the reaction time of the transformation reaction is 24-96 hours.
[0064] Preferably, heating can be performed during the transformation process; the heating temperature is 25℃-95℃.
[0065] This invention provides a high-temperature resistant fluorine-containing ion exchange resin dispersion, wherein the resin dispersion comprises a high-temperature resistant ion exchange resin, an organic solvent, and water.
[0066] The organic solvent is methanol, ethanol, n-propanol, isopropanol, n-butanol, propylene glycol, butanediol, glycerol, aniline, methylamide, tetrahydrofuran, diethylamine, acetaldehyde, cyclohexane, dimethyl sulfoxide, N-methylpyrrolidone, or a mixture thereof.
[0067] In the high-temperature resistant fluorinated ion exchange resin dispersion, the mass fraction of water is 10%-90%, preferably 15%-85%, more preferably 20%-80%, and even more preferably 30%-70%; the mass percentage of the high-temperature resistant functional polymer in the resin dispersion is 1-50%, preferably 5-40%, more preferably 8%-35%, and even more preferably 12-25%; the remaining components are organic solvents.
[0068] The present invention also provides a method for preparing the above-mentioned high-temperature resistant fluorine-containing ion exchange resin dispersion, the method comprising the following steps:
[0069] Step 1: After adding the high-temperature resistant functional polymer to the autoclave, add water and organic solvent, and heat and stir under inert gas protection to dissolve the resin. After the resin is dissolved, stop heating and stirring, and cool to room temperature to obtain a mixed solution.
[0070] Step 2: Separate the mixed solution obtained in Step 1 to obtain a high-temperature resistant fluorine-containing ion exchange resin dispersion.
[0071] In step 1, the inert gas is not particularly limited and can be any conventional inert atmosphere known in the art. For example, it can be an inert atmosphere formed by one or a mixture of nitrogen, argon, or xenon. From a cost perspective, a nitrogen atmosphere is preferred.
[0072] The melting temperature is 100℃-320℃, preferably 120℃-300℃, and more preferably 150℃-250℃.
[0073] More preferably, the heating and dissolving process can be carried out in a closed container at a pressure of 3 MPa-30 MPa, preferably 3.2 MPa-20 MPa, more preferably 3.5 MPa-15 MPa, and even more preferably 4-5 MPa.
[0074] The heating and dissolution time is 1-20 hours, preferably 3-17 hours, and more preferably 4-15 hours.
[0075] In step 2, the separation method includes extraction separation and distillation separation.
[0076] The extraction and separation process involves transferring the mixed solution to a separatory funnel, extracting and separating it using carbon tetrachloride at room temperature and pressure, and then taking the lower layer solution, which is the high-temperature resistant fluorine-containing ion exchange resin dispersion.
[0077] The perfluorosulfonic acid resin dispersion described in this invention can be used to prepare fuel cell catalyst layers, and in similar or identical fields.
[0078] The catalyst layer prepared by the perfluorosulfonic acid resin dispersion of the present invention has high proton conductivity, high exchange capacity and high air permeability, and can operate stably under relatively stable conditions, effectively improving the utilization efficiency of the catalyst.
[0079] The high-temperature resistant fluorinated ion exchange resin dispersion provided by this invention involves a fluorinated ion exchange resin obtained by copolymerization and hydrolysis / acidification of polytetrafluoroethylene, perfluoroethylene phosphonate monomers, perfluorovinyl ether sulfonyl fluoride monomers, and perfluoroheterocyclic olefin ether sulfonyl fluoride monomers. This resin exhibits high chemical and structural stability, high exchange capacity, and good high-temperature mechanical stability. Furthermore, during the preparation of the dispersion, this resin does not easily form undissolved small particles, thus improving the storage stability of the resin dispersion.
[0080] Compared with the prior art, the present invention has at least the following advantages:
[0081] 1. The high-temperature resistant functional polymer provided by the present invention contains perfluoroethylene phosphonic acid polymerization units and two perfluoroolefin sulfonic acid polymerization units with different structures. The three polymerization units work together to solve the problem of high resistivity of resin polymers under high temperature (110℃~150℃) conditions in the prior art. The resistivity of the high-temperature resistant functional polymer provided by the present invention is no higher than 16mS / cm under 150℃ conditions.
[0082] 2. The high-temperature resistant functional polymer provided by this invention can not only start up quickly at low temperatures and maintain high proton conductivity at high temperatures, but also has high air permeability, which perfectly meets the application requirements of catalyst coating.
[0083] 3. The high-temperature resistant functional polymer provided by the present invention uses perfluoroethylene phosphonic acid with no CO bond in the side chain as the polymerization unit, which greatly improves the high-temperature resistance of the resin polymer and further expands the application range of the resin polymer under high-temperature conditions. Attached Figure Description
[0084] Figure 1 The results are from the GPC test of resin polymer F11.
[0085] Figure 2 The results are from the GPC test of resin polymer F22.
[0086] Figure 3 The results are from the GPC test of resin polymer D11.
[0087] Figure 4 The results of the TG test for the precursor polymer F1 obtained in Example 1 are shown below.
[0088] Figure 5 The results of the TG test for the precursor polymer F2 obtained in Example 2 are shown below.
[0089] Figure 6 The TG test results are for the precursor polymer D1 obtained in Comparative Example 1.
[0090] Figure 7 The TG test results are for the precursor polymer D2 obtained in Comparative Example 2.
[0091] Figure 8 The infrared test results are for the precursor polymer F1 obtained in Example 1;
[0092] Figure 9 The infrared test results are for the precursor polymer F2 obtained in Example 2;
[0093] Figure 10 The infrared test results are for the precursor polymer D1 obtained in Comparative Example 1.
[0094] Figure 11 The NMR test results are for the precursor polymer F1 obtained in Example 1;
[0095] Figure 12 The NMR test results are for the precursor polymer F2 obtained in Example 2;
[0096] Figure 13 The NMR results are for the precursor polymer D1 obtained in Comparative Example 1.
[0097] Figure 14 The results are the storage stability test results of the resin dispersions obtained in Examples 3-5. Detailed Implementation
[0098] The following embodiments are further illustrations of the present invention, but the invention is not limited thereto. Unless otherwise specified, the reactors used in each embodiment are 10L stainless steel high-pressure reactors, equipped with temperature sensors, pressure sensors, heating circulation systems, cooling circulation systems, stirring motors, internal cooling water pipes, liquid metering pumps, gas feed valves, liquid feed valves, and material discharge valves from the reactor.
[0099] Unless otherwise specified in the following examples, the ion exchange capacity is the result of the conversion of sulfonyl fluoride to sulfonic acid and phosphonate to phosphorous acid.
[0100] Unless otherwise specified in the examples, all percentages (%) are mass percentages.
[0101] The perfluoroalkyl initiator used in the synthesis process of this invention can be prepared according to techniques known in the art. The preparation method recommended by this invention can be found in J.Org.Chem., 1982, 47(11): 2009-2013.
[0102] The potassium persulfate, ammonium persulfate, and N2F2 gas used in the synthesis process of this invention are all commercially available. Specifically, the potassium persulfate and ammonium persulfate can be purchased from Sinopharm Group; the N2F2 gas can be purchased from Dongyue Chemical Co., Ltd.
[0103] The fluorinated olefin comonomer used in the synthesis process of this invention was purchased from Shandong Dongyue Polymer Materials Co., Ltd.; the perfluorovinyl ether sulfonyl fluoride monomer was prepared using the method described in Chinese patent application number CN201810798170.7; the preparation method of the perfluorovinyl phosphonic acid ester monomer used in the synthesis process of this invention is described in Yamabe M, Akiyama K, Akatsuka Y, et al. Novel phosphonated perfluorocarbon polymers[J]. European Polymer Journal, 2000, 36(5):1035-1041 and Danilich MJ, Burton DJ, Marchant R E. Infrared study of perfluorovinylphosphonic acid, perfluoroallylphosphonic acid, and pentafluoroallyldiethylphosphonate[J].1995,9(3):229-234. The perfluoroheterocyclic olefin ether sulfonyl fluoride monomer was prepared by the methods disclosed in patent numbers: US20090048424A1 and US7799468B2.
[0104] The carbon-supported platinum catalyst powder used in the following examples was purchased from Shanghai Chuxi Industrial Co., Ltd., the polymer long-chain resin electrolyte membrane was the battery membrane of Dongyue Future Hydrogen Energy Materials Co., Ltd. with the brand name DMR100, the support plate was purchased from Qunyi, the gas diffusion layer was Ballard GDS 3260, and the bipolar plate was Qunyi serpentine flow channel.
[0105] Example 1:
[0106] The reactor was cleaned and 5.0L of deionized water and 255g of sodium dodecylbenzenesulfonate were added. The stirring device was turned on, and the reactor was evacuated and purged with high-purity nitrogen three times. After testing and confirming that the oxygen content in the reactor was below 1ppm, the reactor was evacuated again. Then, 1475g of perfluorovinyl ether sulfonyl fluoride monomer (CF2=CF-O-CF2CF2CF2-SO2F), 2356g of perfluorovinyl phosphonate monomer (CF2=CF-CF2-CF2-P=O-(OCH3)2), and 350g of perfluoroheterocyclic olefin ether sulfonyl fluoride were added to the reactor through the liquid feed valve. After monomer addition, tetrafluoroethylene (CF2=CF2) monomer is introduced into the reactor until the pressure reaches 2.8 MPa. The temperature is raised to 55°C, and 450 g of 10% ammonium persulfate aqueous solution is added using a metering pump to initiate the polymerization reaction. Tetrafluoroethylene monomer is continuously introduced to maintain the reaction pressure at 2.8 MPa. After 2 hours of reaction, the addition of initiator is stopped, and the reaction is allowed to continue for 15 minutes before the addition of tetrafluoroethylene monomer is stopped. The reactor is cooled using a cooling circulation system, while unreacted tetrafluoroethylene monomer is recovered using a recovery system. The milky white slurry in the reactor is discharged into the post-processing system through a discharge valve. After high-speed shear demulsification and coagulation, it is filtered to obtain a white polymer powder, which is then dried in a 100°C oven to obtain the precursor polymer F1. The monomer in the filtrate is recovered and reused using the recovery system.
[0107] NMR and infrared analysis confirmed that it is a multi-component precursor resin. The NMR integral value of fluorine shows that the molar percentage of tetrafluoroethylene monomer units in the polymer structure is 60.8%, the molar percentage of sulfonyl fluoride ether monomer units is 15.5%, the molar percentage of cyclic sulfonyl fluoride ether monomer units is 7.7%, and the molar percentage of phosphonate ether monomer units is 16%.
[0108] Infrared spectral analysis: 1468cm -1 The peak at 1217.0 cm⁻¹ represents the vibrational absorption of the sulfonyl fluoride group. -1 The strong absorption peak at 1200 cm⁻¹ is the stretching vibration absorption peak of the P=O group in the phosphonate ester group. -1 and 1148cm -1 The two strongest absorptions are caused by CF vibrations, 720cm -1 and 641cm -1The characteristic peaks belong to the CF2CF2 repeating unit after tetrafluoroethylene copolymerization.
[0109] The TG test showed that the decomposition temperature (Td) of the resin under a nitrogen atmosphere was 382℃.
[0110] Example 2:
[0111] Clean the reactor and add 5.0L of deionized water and 256g of CF2=CF-CF2CF(CF3)-O-CF2CF2-SO3. - NH4 + The stirring device was turned on, and the reactor was evacuated and purged with high-purity nitrogen three times. After testing and confirming that the oxygen content in the reactor was below 1 ppm, the reactor was evacuated again. Then, 1500g of perfluorovinyl ether sulfonyl fluoride monomer (CF2=CF-CF2CF(CF3)-O-CF2CF2-SO2F), 2410g of perfluorovinyl phosphate monomer (CF2=CF-CF2CF2CF2-P=O-(OCH2CH3)2), and 319g of perfluoroheterocyclic olefin ether sulfonyl fluoride were added to the reaction vessel through the liquid feed valve. After monomerization, trifluorochloroethylene (CF2CFCl) monomer was charged into the reactor until the pressure reached 2.8 MPa. The temperature was raised to 55°C, and 10 g of perfluoropropoxypropyl peroxide compound (CF3CF2CF2OCF(CF3)CO-OO-COCF(CF3)OCF2CF2CF3) was added using a metering pump to initiate the polymerization reaction. Trifluorochloroethylene monomer was continuously introduced to maintain the reaction pressure at 2.8 MPa. 2.0 g of initiator was added to the system every 20 min. After the reaction was carried out for 2.5 h, the addition of initiator was stopped, and the reaction was allowed to continue for 20 min before the addition of trifluorochloroethylene monomer was stopped. The reactor is cooled by a cooling circulation system, while unreacted trifluorochloroethylene monomer is recovered by a recovery system. The milky white slurry in the reactor is discharged into the post-processing system through a discharge valve. After high-speed shear demulsification and coagulation, it is filtered to obtain white polymer powder, which is then dried in a 100°C oven to obtain polymer F2 containing both sulfonyl fluoride and phosphonate side groups. After hydrolysis and acidification, an ionic polymer containing sulfonic acid and phosphate groups is obtained. The monomer in the filtrate is recovered and reused by the recovery system.
[0112] Polymer data: The total ion exchange capacity of the resin is 1.32 mmol / g dry resin. The polymer structure contains 68.4% fluorinated olefin polymer units, 8.8% sulfonyl fluorinated ether polymer units, 8.5% cyclic sulfonyl fluorinated ether polymer units, and 14.3% phosphonate ether polymer units.
[0113] IR spectrum: 1471 cm⁻¹ -1 This is the absorption peak of the S=O vibration in sulfonyl fluoride; 1219 cm⁻¹-1 This is the absorption peak of the P=O vibration in phosphonates; 986 cm⁻¹ -1 Caused by -CF3 vibration; 1205 and 1150 cm -1 The two strongest absorptions are caused by the -CF vibration; 720 cm⁻¹ -1 645cm -1 This is caused by the absorption of the -CF2-CFCl- vibration after copolymerization of trifluorochloroethylene.
[0114] The TG test showed that the decomposition temperature (Td) of the resin under a nitrogen atmosphere was 385℃.
[0115] Comparative Example 1
[0116] In this example, the perfluorovinyl phosphonate monomer in Example 1 was replaced with a perfluorovinyl ether phosphonate monomer (CF2=CF-O-CF2-CF2-P=O-(OCH3)2), and the remaining components and preparation process were the same as in Example 1, resulting in polymer D1.
[0117] NMR and infrared analysis confirmed that it is a multi-component precursor resin. The NMR integral value of fluorine showed that the molar percentage of tetrafluoroethylene monomer units in the polymer structure was 63.2%, the molar percentage of sulfonyl fluoride ether monomer units was 12.6%, the molar percentage of cyclic sulfonyl fluoride ether monomer units was 8.9%, and the molar percentage of phosphonate ether monomer units was 15.3%.
[0118] Infrared spectral analysis: 1469cm -1 The peak at 1219.0 cm⁻¹ represents the vibrational absorption of the sulfonyl fluoride group. -1 The strong absorption peak is the stretching vibration absorption peak of the phosphonate group at P=0, 1204 cm⁻¹. -1 and 1149cm -1 The two strongest absorptions are caused by CF vibrations, 720cm -1 and 641cm -1 The characteristic peaks belong to the CF2CF2 repeating unit after tetrafluoroethylene copolymerization.
[0119] The TG test showed that the decomposition temperature (Td) of the resin under a nitrogen atmosphere was 342℃.
[0120] Comparative Example 2
[0121] The reactor was cleaned and 5.0L of deionized water and 255g of sodium dodecylbenzenesulfonate were added. The stirring device was turned on, and the reactor was evacuated and purged with high-purity nitrogen three times. After testing that the oxygen content in the reactor was below 1ppm, the reactor was evacuated again. 1475g of perfluorovinyl ether sulfonyl fluoride monomer (CF2=CF-O-CF2CF2CF2-SO2F) was added into the reactor through the liquid feed valve. Tetrafluoroethylene (CF2=CF2) monomer was added into the reactor until the pressure reached 2.8MPa. The temperature was raised to 55℃, and 450g of 10% ammonium persulfate aqueous solution was added using a metering pump to initiate the polymerization reaction. Tetrafluoroethylene monomer was continuously introduced to maintain the reaction pressure at 2.8MPa. After 2 hours of reaction, the addition of initiator was stopped, and the reaction was allowed to continue for 15 minutes before the addition of tetrafluoroethylene monomer was stopped. The reactor is cooled by a cooling circulation system, and unreacted tetrafluoroethylene monomer is recovered by a recovery system. The milky white slurry in the reactor is fed into the post-processing system through a discharge valve. After high-speed shearing demulsification and coagulation, it is filtered and separated to obtain white polymer powder, which is then dried in a 100°C oven to obtain a copolymer of perfluorovinyl ether sulfonyl fluoride and tetrafluoroethylene.
[0122] The reactor was cleaned and 5.0L of deionized water and 255g of sodium dodecylbenzenesulfonate were added. The stirring device was turned on, and the reactor was evacuated and purged with high-purity nitrogen three times. After testing that the oxygen content in the reactor was below 1ppm, the reactor was evacuated again. 1475g of perfluorovinylphosphonate monomer (CF2=CF-CF2-CF2-P=O-(OCH3)2) was added into the reactor through the liquid feed valve. Tetrafluoroethylene (CF2=CF2) monomer was added into the reactor until the pressure reached 2.8MPa. The temperature was raised to 55℃, and 450g of 10% ammonium persulfate aqueous solution was added using a metering pump to initiate the polymerization reaction. Tetrafluoroethylene monomer was continuously introduced to maintain the reaction pressure at 2.8MPa. After 2 hours of reaction, the addition of initiator was stopped, and the reaction was allowed to continue for 15 minutes before the addition of tetrafluoroethylene monomer was stopped. The reactor is cooled by a cooling circulation system, and unreacted tetrafluoroethylene monomer is recovered by a recovery system. The milky white slurry in the reactor is fed into the post-processing system through a discharge valve. After high-speed shearing demulsification and coagulation, it is filtered and separated to obtain white polymer powder, which is then dried in a 100°C oven to obtain a perfluorovinyl phosphonate-tetrafluoroethylene copolymer.
[0123] The reactor was cleaned and 5.0L of deionized water and 255g of sodium dodecylbenzenesulfonate were added. The stirring device was turned on, and the reactor was evacuated and purged with high-purity nitrogen three times. After testing that the oxygen content in the reactor was below 1ppm, the reactor was evacuated again. 350g of perfluoroheterocyclic olefin ether sulfonyl fluoride (CF2=CF-O-CF2CF2CF2-SO2F) was added into the reactor through the liquid feed valve. Tetrafluoroethylene (CF2=CF2) monomer was added into the reactor until the pressure reached 2.8MPa. The temperature was raised to 55℃, and 450g of 10% ammonium persulfate aqueous solution was added using a metering pump to initiate the polymerization reaction. The tetrafluoroethylene monomer was continuously introduced to maintain the reaction pressure at 2.8MPa. After 2 hours of reaction, the addition of initiator was stopped, and the reaction was allowed to continue for 15 minutes before the addition of tetrafluoroethylene monomer was stopped. The reactor is cooled by a cooling circulation system, and unreacted tetrafluoroethylene monomer is recovered by a recovery system. The milky white slurry in the reactor is fed into the post-processing system through a discharge valve. After high-speed shearing demulsification and coagulation, it is filtered and separated to obtain white polymer powder, which is then dried in a 100°C oven to obtain a copolymer of perfluoroheterocyclic olefin ether sulfonyl fluoride and tetrafluoroethylene.
[0124] This comparative example does not involve copolymerization. Instead, the obtained perfluorovinyl ether sulfonyl fluoride copolymer with tetrafluoroethylene, perfluorovinyl phosphonate copolymer with tetrafluoroethylene, and perfluoroheterocyclic olefin ether sulfonyl fluoride copolymer with tetrafluoroethylene are blended and granulated at 380°C to obtain D2. TG testing of D2 revealed that it has three thermal decomposition temperatures, indicating that the blending of only three materials cannot withstand high temperatures.
[0125] Application example:
[0126] This application example is used in the chemical treatment process of the precursor polymers F1, F2, D1, D2 obtained from the polymerization of Examples 1-2 and Comparative Examples 1 and 2.
[0127] Fluorine-containing ion exchange polymers containing sulfonyl fluoride and phosphonate groups were added to a 15% sodium hydroxide solution and soaked for 15 hours at 80°C. The precursor polymers were then placed in a container and rinsed with pure water until pH=7 at 45°C. After drying at 80°C, a basic fluorine-containing ion exchange resin was obtained. This basic fluorine-containing ion exchange resin was then soaked in a 20% nitric acid solution and heated to 85°C. After 10 acid changes, resin polymers F11, F22, D11, and D22 were obtained.
[0128] The performance of the above-mentioned resin polymers F11, F22, D11, and D22 was tested, including ion exchange capacity, gas permeability, and resistivity. The resistivity test method followed GB / T20042.3-2009 Proton Exchange Membrane Fuel Cells Part 3: Test Methods for Proton Exchange Membranes. The thermal decomposition temperature was determined using thermogravimetric analysis. Specifically, the test method involved heating from room temperature to 600℃ at a rate of 10℃ / min under a nitrogen atmosphere. Figure 5 and Figure 6 ) or 525℃ Figure 6 and Figure 7 The thermal decomposition temperature is determined by extrapolation from the thermogravimetric curve.
[0129] The thermal decomposition temperature of D11 was tested to be 375℃. Performance data for the remaining resin polymers are shown in Table 1.
[0130] Table 1 Performance data of resin polymers
[0131]
[0132] Example 3:
[0133] Prepare a 2 kg mixture of water, n-propanol, and propylene glycol, wherein the water mass fraction is 55% and the mass ratio of n-propanol to propylene glycol is 1:1. Add 400 g of the high-temperature resistant functional polymer prepared in Example 1 to the above mixed solvent, then transfer it to an autoclave, seal it, and stir under nitrogen protection. Heat to 180°C, maintain the temperature for 8 hours, cool to room temperature, remove the mixed solution, and separate it by carbon tetrachloride extraction at room temperature and pressure. Remove the lower layer solution. This yields a high-temperature resistant fluorine-containing ion exchange resin dispersion. Visually, no insoluble matter is found in the dispersion.
[0134] A catalyst-containing slurry was prepared by mixing 8.7% carbon-supported platinum catalyst powder (platinum content 40%), 59.6% water, 22.3% ethanol, and 9.4% propylene glycol. A catalyst ink was prepared by mixing a resin dispersion with the catalyst-containing slurry (resin dispersion to slurry mass ratio 1:5). After thorough mixing of the catalyst ink by ball milling, it was wire-coated onto a polytetrafluoroethylene sheet. The catalyst layer was transferred to the surface of a composite proton exchange membrane at 120℃ and 1 MPa, resulting in a platinum loading of 0.3 mg / cm³. 2 The membrane electrode.
[0135] Example 4:
[0136] Prepare a 2 kg mixture of water, ethanol, and dimethylformamide, wherein the water content is 33% by mass, and the mass ratio of ethanol to dimethylformamide is 4:1. Add 450 g of the resin prepared in Example 1 to the above mixture, transfer it to an autoclave, seal it, and stir under nitrogen protection. Heat to 220°C, maintain the temperature for 5 hours, cool to room temperature, remove the mixture, and separate it by carbon tetrachloride extraction at room temperature and pressure. Remove the lower layer solution to obtain the perfluorosulfonic acid resin dispersion. Visually, no insoluble matter is found in the dispersion.
[0137] Following the membrane electrode preparation method of Example 3, a platinum loading of 0.3 mg / cm² was prepared. 2 The membrane electrode.
[0138] Example 5:
[0139] Prepare a 2 kg mixture of water, methanol, and tetrahydrofuran, wherein the water mass fraction is 47% and the methanol to tetrahydrofuran mass ratio is 5:1. Add 490 g of the resin prepared in Example 1 to the above mixture, transfer it to an autoclave, seal it, and stir under nitrogen protection. Heat to 280°C, maintain the temperature for 7 hours, cool to room temperature, remove the mixture, and separate it by carbon tetrachloride extraction at room temperature and pressure. Remove the lower layer solution to obtain the perfluorosulfonic acid resin dispersion. Visually, no insoluble matter is found in the dispersion.
[0140] Following the membrane electrode preparation method of Example 3, a platinum loading of 0.3 mg / cm² was prepared. 2 The membrane electrode.
[0141] Comparative Example 3
[0142] Prepare a 2 kg mixed solution of water and ethanol, wherein the water mass fraction is 50%, and add a perfluorosulfonic acid resin with an exchange capacity of 1.1 mmol / g (resin structure is...). (490g), then transferred to an autoclave, sealed, and stirred under nitrogen protection. The mixture was heated to 200℃, kept at that temperature for 7 hours, and then cooled to room temperature. The mixed solution was removed, and after extraction and separation by carbon tetrachloride at room temperature and pressure, the lower layer solution was removed, yielding the perfluorosulfonic acid resin dispersion. Visual inspection revealed no insoluble matter in the dispersion.
[0143] 60% of the carbon-supported platinum catalyst powder, water, isopropanol, and the resin solution obtained above were mixed and stirred under ultrasonic oscillation to obtain the electrode catalyst ink. The electrode catalyst ink was then coated onto both sides of a polymer electrolyte membrane using an automatic screen printing machine, resulting in a platinum loading of 0.3 mg / cm³. 2 MEA.
[0144] Comparative Example 4
[0145] Prepare a 2 kg mixed solution of water and n-propanol, wherein the water mass fraction is 60%, and add a perfluorosulfonic acid resin with an exchange capacity of 1.2 mmol / g (resin structure is...). (450g), then transferred to an autoclave, sealed, and stirred under nitrogen protection. Heated to 180℃ and held for 6 hours, then cooled to room temperature. The mixed solution was removed and separated by carbon tetrachloride extraction at room temperature and pressure. The lower layer solution was then removed, yielding the perfluorosulfonic acid resin dispersion. Visual inspection revealed no insoluble matter in the dispersion.
[0146] Following the membrane electrode preparation method of Example 1, a platinum loading of 0.3 mg / cm² was prepared. 2 The membrane electrode.
[0147] Impedance, solid content, and micelle size were tested on the samples in the examples and comparative examples, respectively, using the following methods:
[0148] 1. Diffusion impedance test:
[0149] Fabrication of a single fuel cell: The same gas diffusion layer, bipolar plate, and support plate are stacked on both sides of the membrane electrode obtained in the examples or comparative examples to form a fuel cell.
[0150] The aforementioned fuel cell was placed in the Qunyi 850Es fuel cell evaluation device to conduct a local transmission impedance test experiment.
[0151] The experimental conditions are as follows: (1) The battery temperature is 90℃, humidified at 100%RH, and the voltage is stabilized at 0.15V for 20 minutes under pressures of 0KPa, 50KPa, 100KPa, 150KPa, and 200KPa respectively. The final stable current density value is then taken. (2) The battery temperature is 90℃, pressure is 0KPa, and the voltage is stabilized at 0.15V for 20 minutes under humidity conditions of 10%RH, 30%RH, 50%RH, 70%RH, and 100%RH respectively. The final stable current density value is then taken.
[0152] The molecular diffusion impedance, Knudsen diffusion impedance, and local ionomer diffusion impedance were obtained through the above experimental simulation fitting. The molecular diffusion impedance is the impedance of the gas diffusion layer, the Knudsen diffusion impedance is caused by the catalyst layer, and the local ionomer diffusion impedance is caused by the ionomers in the catalyst layer.
[0153] 2. Solid content of resin dispersion: tested using a halogen moisture analyzer.
[0154] 3. Micelle particle size: The micelle particle size of the dispersion was measured by a Brookhaven particle size analyzer. The smaller the micelle particle size in the dispersion, the more uniformly the catalyst is dispersed in the solvent, which is more conducive to the formation of the three-phase interface of the catalyst and effectively improves the proton conductivity of the catalyst layer.
[0155] The sample test results are summarized in Table 2.
[0156] The storage stability results of the resin dispersions in Examples 1-3 are as follows: Figure 2 As shown.
[0157] Table 2. Performance data of resin solutions and catalyst layers in Examples 3-5 and Comparative Examples 3-4.
[0158]
Claims
1. A high-temperature resistant fluorinated ion exchange resin dispersion, characterized in that, The resin dispersion is composed of high-temperature resistant fluorine-containing ion exchange resin, organic solvent, and water. The high-temperature resistant fluorine-containing ion exchange resin has a mass percentage of 1-50% in the resin dispersion, the water has a mass fraction of 10%-90%, and the remaining components are organic solvents. The high-temperature resistant fluorine-containing ion exchange resin is obtained by copolymerizing a precursor polymer of fluorine-containing olefins, perfluoroethylene phosphonate monomers, perfluorovinyl ether sulfonyl fluoride monomers, and perfluoroheterocyclic olefin ether sulfonyl fluoride monomers, followed by hydrolysis and acidification. The structural formula of the high-temperature resistant fluorine-containing ion exchange resin is as follows: in, g is an integer from 1 to 4; t is an integer from 0 to 3, and v is an integer from 1 to 4; a, b, and c are integers from 1 to 20, and a', b', and c' are integers from 1 to 3. x / (x+y+z)=0.6-0.8, y / (x+y+z)=0.1-0.2, z / (x+y+z)=0.1-0.2; R is —(OCF2) e (CF2) f X, where X is Cl or F, e is an integer from 0 to 1, and f is an integer from 0 to 1; R1 is ,or ; R f for ,or ,or ,or , Where m and n are integers from 0 to 4, and m and n are not both 0.
2. The high-temperature resistant fluorine-containing ion exchange resin dispersion according to claim 1, characterized in that, In the high-temperature resistant fluorine-containing ion exchange resin dispersion, the mass fraction of water is 15%-85%, and the mass percentage of the high-temperature resistant fluorine-containing ion exchange resin is 5%-40%.
3. The high-temperature resistant fluorine-containing ion exchange resin dispersion according to claim 2, characterized in that, The water content is 20%-80% by mass, and the high-temperature resistant fluorinated ion exchange resin content is 8%-35% by mass.
4. The high-temperature resistant fluorine-containing ion exchange resin dispersion according to claim 2, characterized in that, The water content is 30%-70% by mass, and the high-temperature resistant fluorinated ion exchange resin content is 12%-25% by mass.
5. The high-temperature resistant fluorine-containing ion exchange resin dispersion according to claim 1, characterized in that, The organic solvent is one or a mixture of methanol, ethanol, n-propanol, isopropanol, n-butanol, propylene glycol, butanediol, glycerol, aniline, methylamide, tetrahydrofuran, diethylamine, cyclohexane, dimethyl sulfoxide, and N-methylpyrrolidone.
6. The high-temperature resistant fluorinated ion exchange resin dispersion according to claim 5, characterized in that, The organic solvent is a mixture of two of the following: methanol, ethanol, n-propanol, propylene glycol, tetrahydrofuran, and dimethylformamide.
7. The high-temperature resistant fluorinated ion exchange resin dispersion according to claim 5, characterized in that, The organic solvent is one of the following: a mixture of methanol and tetrahydrofuran, a mixture of ethanol and dimethylformamide, or a mixture of n-propanol and propylene glycol.
8. The high-temperature resistant fluorine-containing ion exchange resin dispersion according to claim 1, characterized in that, The number-average molecular weight of the high-temperature resistant fluorinated ion exchange resin is 100,000 to 600,000.
9. The high-temperature resistant fluorinated ion exchange resin dispersion according to claim 8, characterized in that, The number-average molecular weight of the high-temperature resistant fluorinated ion exchange resin is 150,000 to 400,000.
10. The high-temperature resistant fluorinated ion exchange resin dispersion according to claim 8, characterized in that, The number-average molecular weight of the high-temperature resistant fluorinated ion exchange resin is 200,000 to 370,000.
11. The high-temperature resistant fluorinated ion exchange resin dispersion according to claim 1, characterized in that, The percentage of molar content of each polymer unit in the precursor polymer is as follows: 60-80% of the total molar content of fluorinated olefin polymer units, 5-20% of the total molar content of perfluoroethylene phosphonate polymer units, 5-20% of the total molar content of perfluorovinyl ether sulfonyl fluoride polymer units, and 5-20% of the total molar content of perfluoroheterocyclic olefin ether sulfonyl fluoride polymer units.
12. The high-temperature resistant fluorinated ion exchange resin dispersion according to claim 11, characterized in that, The percentage of molar content of each polymer unit in the precursor polymer is as follows: 70-80% of the total molar fraction of fluorinated olefin polymer units, 6-20% of the total molar fraction of perfluorinated vinyl ether sulfonyl fluoride polymer units, 6-20% of the total molar fraction of perfluorinated heterocyclic olefin ether sulfonyl fluoride polymer units, and 6-20% of the total molar fraction of perfluorinated phosphonate polymer units.
13. The method for preparing the high-temperature resistant fluorinated ion exchange resin dispersion according to any one of claims 1 to 12, characterized in that, Includes the following steps: Step 1: After adding the high-temperature resistant fluorine-containing ion exchange resin to the autoclave, add water and organic solvent, and heat and stir under inert gas protection to dissolve the resin. After the resin is dissolved, stop heating and stirring, and cool to room temperature to obtain a mixed solution. Step 2: Separate the mixed solution obtained in Step 1 to obtain a high-temperature resistant fluorine-containing ion exchange resin dispersion.
14. The preparation method according to claim 13, characterized in that, The dissolution temperature described in step 1 is 100℃-320℃.
15. The preparation method according to claim 14, characterized in that, The dissolution temperature described in step 1 is 120℃-300℃.
16. The preparation method according to claim 14, characterized in that, The dissolution temperature described in step 1 is 150℃-250℃.
17. The preparation method according to claim 13, characterized in that, The dissolution described in step 1 is carried out in a closed container at a pressure of 3.2 MPa-20 MPa.
18. The preparation method according to claim 17, characterized in that, The pressure is 3.5MPa-15MPa.
19. The preparation method according to claim 17, characterized in that, The pressure is 4-5 MPa.
20. The preparation method according to claim 13, characterized in that, The dissolution time for step 1 is 1-20 hours.
21. The preparation method according to claim 20, characterized in that, The dissolution time for step 1 is 3-17 hours.
22. The preparation method according to claim 20, characterized in that, Step 1 dissolution time: 4-15 hours.
23. The preparation method according to claim 13, characterized in that, The separation methods include extraction separation and distillation separation.
Citation Information
Patent Citations
Preparation method of perfluorovinyl ether sulfonyl fluoride
CN108863854A
Phosphorylated polyvinyl alcohol / perfluorosulfonic acid resin compound and ion exchange membrane
CN113429715A
Boat loading guiding system
US10351041B2
Dual century calendar
US2000365A
Fluorosulfonyl group-containing monomer and its polymer, and sulfonic acid group-containing polymer
US20090048424A1